Canonical Wnt Signaling Induces Vascular Endothelial Dysfunction via p66 Shc -Regulated Reactive Oxygen Species - Ajit Vikram; Young‐Rae Kim; Santosh Kumar; Asma Naqvi; Timothy A. Hoffman; Ajay Kumar; Francis J. Miller; Cuk‐Seong Kim; Kaikobad Irani (2014)
Objective— Reactive oxygen species regulate canonical Wnt signaling. However, the role of the redox regulatory protein p66 Shc in the canonical Wnt pathway is not known. We investigated whether p66 Shc is essential for canonical Wnt signaling in the endothelium and determined whether the canonical Wnt pathway induces vascular endothelial dysfunction via p66 Shc -mediated oxidative stress. Approach and Results— The canonical Wnt ligand Wnt3a induced phosphorylation (activation) of p66 Shc in endothelial cells. Wnt3a-stimulated dephosphorylation of β-catenin, and β-catenin–dependent transcription, was inhibited by knockdown of p66 Shc . Exogenous H 2 O 2 -induced β-catenin dephosphorylation was also mediated by p66 Shc . Moreover, p66 Shc overexpression dephosphorylated β-catenin and increased β-catenin–dependent transcription, independent of Wnt3a ligand. P66 Shc -induced β-catenin dephosphorylation was inhibited by antioxidants N-acetyl cysteine and catalase. Wnt3a upregulated endothelial NADPH oxidase-4, and β-catenin dephosphorylation was suppressed by knocking down NADPH oxidase-4 and by antioxidants. Wnt3a increased H 2 O 2 levels in endothelial cells and impaired endothelium-dependent vasorelaxation in mouse aortas, both of which were rescued by p66 Shc knockdown. P66 Shc knockdown also inhibited adhesion of monocytes to Wnt3a-stimulated endothelial cells. Furthermore, constitutively active β-catenin expression in the endothelium increased vascular reactive oxygen species and impaired endothelium-dependent vasorelaxation. In vivo, high-fat diet feeding–induced endothelial dysfunction in mice was associated with increased endothelial Wnt3a, dephosphorylated β-catenin, and phosphorylated p66 Shc . High-fat diet–induced dephosphorylation of endothelial β-catenin was diminished in mice in which p66 Shc was knocked down. Conclusions— p66 Shc plays a vital part in canonical Wnt signaling in the endothelium and mediates Wnt3a-stimulated endothelial oxidative stress and dysfunction